2020
DOI: 10.1155/2020/8852847
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cepacia Sepsis in a Previously Healthy Full-Term Infant

Abstract: Burkholderia cepacia causes sepsis in neonates who are immunocompromised or exposed via nosocomial transmission. We report a case of B. cepacia sepsis in a previously healthy 5-week-old male originally treated for bacterial pneumonia per chest X-ray findings and 3 days of fevers. Regardless of appropriate antibiotics and an initial negative blood culture, he developed severe hypoglycemia, circulatory collapse with disseminated intravascular coagulopathy, and expired. A second blood culture taken following tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Burkholderia cepacia , a potential pathogen, was identified in one term sample (relative abundance 50.6%) and two preterm samples (relative abundances of 11.3% and 1.04%). This species has previously been reported as a cause of neonatal sepsis in a full term infant [ 39 ], while other species of the genus have been reported to cause intra-amniotic infection and preterm labour [ 40 , 41 ]. The results of our study therefore highlight the potential to detect preterm-birth-associated pathogens in amniotic fluid samples taken early in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia cepacia , a potential pathogen, was identified in one term sample (relative abundance 50.6%) and two preterm samples (relative abundances of 11.3% and 1.04%). This species has previously been reported as a cause of neonatal sepsis in a full term infant [ 39 ], while other species of the genus have been reported to cause intra-amniotic infection and preterm labour [ 40 , 41 ]. The results of our study therefore highlight the potential to detect preterm-birth-associated pathogens in amniotic fluid samples taken early in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of healthcare-associated BCC outbreaks, medical products are found to be the most frequent source of the outbreaks, representing over half of the identified sources, with 12% of the outbreaks caused by disinfectant products [ 16 ]. Maternal risk factors such as poor intrapartum and postnatal infection control practices also play a role in developing neonatal infections [ 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these organisms are E. coli or Klebsiella isolates; however, other gram-negatives have emerged as multidrug-resistant threats. These multidrug-resistant GNB run the gamut from common pathogens such as Salmonella and Serratia all the way to Ewingella, Elizabethkingia, Pantoea, and Chryseobacterium spp [30][31][32][33][34][35][36][37][38][39][40]. Perhaps the most concerning trend in gram-negative neonatal infections has been the arrival of carbapenem-resistant organisms [41].…”
Section: Gram-negativementioning
confidence: 99%